Whipple’s Disease – a clinical case-report - Santos, Eugénia (2002)
We describe a case of Whipple’s disease in which a Jarisch-Herxheimer reaction occurred. Diagnosis was made in the standard way: histology. We then discuss this case with update information on pathogenesis, diagnosis, treatment and follow-up of this rare but possibly fatal illness if left untreated, namely the immune defect and the new diagnostic methods such as the PCR technique and the immunofluorescenceserologic test.